(untitled) - Mankins, Michael (Boston, Massachusetts, 2017)
Business leaders know that the key to competitive success is smart management of scarce resources. That's why companies allocate their financial capital so carefully. But capital today is cheap and abundant, no longer a source of advantage. The truly scarce resources now are the time, the talent, and the energy of the people in your organization--resources that are too often squandered. There's plenty of advice about how to manage them, but most of it focuses on individual actions. What's really needed are organizational solutions that can unleash a company's full productive power and enable it to outpace competitors. Building off of the popular Harvard Business Review article, "Your Scarcest Resource," Michael Mankins and Eric Garton, Bain & Company experts in organizational design and effectiveness, present new research into how you can liberate people's time, talent, and energy and unleash your organization's productive power. They identify the specific causes of organizational drag--the collection of institutional factors that slow things down, decrease output, and drain people's energy--and then offer a simple framework for how managers can overcome it. With practical advice for using the framework and in-depth examples showing how the best companies manage their people's time, talent, and energy with as much discipline as they do their financial capital, this book shows managers how to create a virtuous circle of high performance.
Keywords: Quản trị nhân sự,Personnel management